Juridical Analysis of Alleged Provision of False Information in Pretrial Corruption Cases of e-KTP - Rustam HS Akili (LEGAL BRIEF, 2022)
On April 5 2017, the KPK named Miryam S Haryani as a suspect in the alleged corruption case of e-KTP with Investigation Order No. Sprint Dik-28/01/04/2017. For her actions, Miryam is suspected of violating Article 22 in conjunction with Article 35 of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. On April 20, 2017, Miryam's legal team submitted a pretrial application stating that the KPK's determination of a suspect against his client was contrary to the law and the provisions of the applicable procedural law, because: a. The KPK does not have the authority to carry out investigations and investigations related to Article 22 of the Anti-Corruption Law, because Article 22 is regulated in Chapter III which is about other criminal acts related to corruption, so this is not the task and authority of the KPK as regulated in Article 6 Chapter II. KPK Law; b. The investigation into the criminal act of giving false information before the court is carried out based on article 174 of the Criminal Procedure Code; c. the determination of the suspect in the name of Miryam S Haryani was issued without two valid pieces of evidence. This study aims to determine the legal basis for determining the suspect as a pretrial object associated with the alleged criminal act of giving false information by Miryam S Haryani and to find out the authority of the KPK in investigating the case of the crime of giving false information by Miryam S Haryani in the e-KTP corruption case that was submitted for pretrial. at the South Jakarta District Court. The research method used is normative juridical, which is an approach to literature review as secondary data. The results of the study are, the legal basis for determining the suspect as an object of pretrial is the decision of the Constitutional Court no. 21/PUU-XII/2014 dated 28 April 2015, which provides prerequisites for the determination as a suspect, namely that a minimum of two pieces of evidence must be met as contained in Article 184 of the Criminal Procedure Code. If it is related to the alleged criminal act of giving false information by Miryam S Haryani, the pretrial application for the case number 47/Pid/Pra/2017/PN. Jkt. Sel, the determination of the suspect against Miryam S Haryani has been based on more than 2 (two) pieces of evidence.